Pastorship in Byzantium in the letters of St. Theodore the Studite (late 8th — early 9th centuries) - Olga Izotova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines various aspects of shepherdship mentioned by St. Theodore the Studite in the collection of his letters. The collection contains letters sent to patriarchs, bishops, abbots and abbesses, as well as their flocks. There are few letters to priests and they do not touch on pastoral topics, in contrast to the epistles to the bishops that multiplied after 815. Among them, it is necessary to mention the letter 11 to bishop Anastasius, as a text completely devoted to the episcopal ministry. In total, there are more than fifty letters to the bishops, and a little less than eighty to the heads of the monasteries. The correspondence of St. Theodore with Mother Superior Euphrosyne is especially interesting. Descripting the episcopal ministry, St. Theodore makes extensive use of the teachings of St. Gregory the Theologian, and when talking about pastoral qualities works of St. Maximus the Confessor. Despite not the fact that St. Theodore often uses the word "pastor" simply to designate a ruler, bishop or abbot, it is not just a designation of the holy dignity for him, but the title of shepherd can be received by one owing to his deeds. The basis of shepherding, from the point of view of St. Theodore, there must be a realization in oneself of the image of Christ, the image of a virtuous life, approaching God, the realization of the pastoral logos in the right way, the acquisition of a disposition towards spiritual life. A shepherd who does this is capable of being a legislator for his disciples, capable of raising their souls to God. An important aspect of pastoral ministry for St. Theodora - accepting this service as obedience and service of love.